THE SCIENTIFIC ANALYSIS OF ZAMZAM WATER IN THE PERSPECTIVE OF HADITH PROPHET MUHAMMAD SAW - Lutfiah, Husna (AS-SALAM, 2020)
This research is motivated by the rapid development of natural science and research conducted by scientists. We already know that Zamzam water is the best water on earth according to the hadith of the prophet Muhammad SAW. Therefore, the authors are interested in researching and examining more deeply about Zamzam water based on the hadith of the Prophet Muhammad and science. This research is a library research with primary data source in the form of Complete Hadith Index by Ahmad Zacky El-Syafa and supported by international journals. The data management technique uses qualitative data analysis, while the data analysis techniques and steps are to describe, collect and describe.